An International marketing case study - Frederick, Chris David (KDI School, 1999)
During the 1990''s British retailer Marks & Spencer was obsessed with expansion, particularly in Asia, where it planned to increase its presence by 300% before the year 2000. After expanding to nearly every country in Southeast Asia it was only natural to view North East Asia as the next target. Anticipating full retail liberalization, Marks & Spencer (M&S) officials arrived in Seoul in 1994 to begin work on a feasibility study for possible entry into the Korean market. When the decision was made to enter, Kim Sung Joo of Sun Joo International was awarded the franchise for Korea. It has been suggested that the Korean Financial crisis was the main culprit in the near demise of Marks and Spencer in Korea, but this paper argues differently. This study suggests that Marks & Spencer joins a long list of foreign companies that didn''t take the time to understand the Korean market and the resources needed to succeed. This study suggests flaws in strategy and marketing were present from the outset, and these were substantial enough to deal a deathblow to the operations without the assistance of a financial meltdown. This paper has several objectives. First, is to present a case study of international marketing. Second, to analyze the social, economic, and market conditions of Korea in the mid-1990''s so the reader can fully appreciate Marks and Spencer''s operating environment. Third, to explain the retail liberalization polices which allowed Mark''s and Spencer to conduct business in Korea. Lastly, to present and asses Marks and Spencer''s strategy for the Korea, with emphasis on marketing.
Thesis(Master) --KDI School:Master of Strategy & International Management,1999